Sequential Venous Percutaneous Transluminal Angioplasty and Balloon Dilatation of the Interatrial Septum during Percutaneous Edge-to-Edge Mitral Valve Repair - Jorbenadze, Rezo (Case Rep Cardiol, 2017)
Percutaneous edge-to-edge mitral valve repair (PMVR) is widely used for selected, high-risk patients with severe mitral valve regurgitation (MR). This report describes a case of 81-year-old woman presenting with severe and highly symptomatic mitral valve regurgitation (MR) caused by a flail of the posterior mitral valve leaflet (PML). PMVR turned out to be challenging in this patient because of a stenosis and tortuosity of both iliac veins as well as sclerosis of the interatrial septum, precluding the vascular and left atrial access by standard methods, respectively. We managed to achieve atrial access by venous percutaneous transluminal angioplasty (PTA) and balloon dilatation of the interatrial septum. Subsequently, we could advance the MitraClip® system to the left atrium, and deployment of the clip in the central segment of the mitral valve leaflets (A2/P2) resulted in a significant reduction of MR.